Exploring the Influence of Top Management Support on the Relationship between Workplace Deviance Dimensions And Job Satisfaction in Omani Universities - ALBUSAIDI, Mohammed Juma Khalifa; Islam, Muhummad Khairul; JAAFFAR, Amar Hisham; KHUDARI, Mohamed (Journal of Ecohumanism, 2025)
Purpose – This paper aims to examine the influence of workplace deviance dimensions on job satisfaction, with Top Management support acting as a mediator within Omani universities. Research Methodology—The study’s data were collected using a random sampling method, encompassing employees and academic staff from various universities in Oman. The sample size of 380 respondents was analysed using Structural Equation Modelling (Smart-PLS) to explore causal relationships among the study’s latent variables. Findings – The findings indicate that several workplace deviance factors—specifically communication, training development, employee empowerment, diversity tolerance, and employee motivation—are significant negative predictors of job satisfaction. However, work stress did not show a significant effect on job satisfaction. Additionally, a lack of communication, training development, and employee motivation had a statistically significant negative impact on top management support, whereas employee empowerment had a positive impact. Conversely, work stress and lack of diversity tolerance were found to be insignificant for top management support. Top management support (TM) was found to mediate the relationship between workplace deviance and job satisfaction. Specifically, TM partially mediated the lack of communication, training development, and employee empowerment on job satisfaction. The major contribution of this research lies in statistically validating the negative influence of workplace deviance factors on job satisfaction within the higher education sector in Oman. Practical implications – This study enhances understanding the relationships between workplace stress, communication, training development, diversity tolerance, and employee motivation, offering essential guidelines for managing workplace deviance. Originality/Value –It contributes to the ongoing discourse on the critical role of top management support by examining its unique mediating effect on workplace deviance and job satisfaction.